Solid peroxides in Fenton-like reactions at near neutral pHs: Superior performance of MgO2 on the accelerated reduction of ferric species. (May 2021) - Zhu, Yitong; Qin, Jiaolong; Zhang, Shuqi; Radian, Adi; Long, Mingce
Abstract: Fenton-like reactions at near neutral pHs are limited by the slow reduction of ferric species. Enhancing generation of from solid peroxides is a promising strategy to accelerate the rate-limiting step. Herein, the H2 O2 release and Fenton-like reactions of four solid peroxides, MgO2, CaO2, ZnO2 and urea hydrogen peroxide (UHP), were investigated. Results indicated that UHP can release H2 O2 instantly and show a similar behavior as H2 O2 in the Fenton-like reactions. MgO2 released H2 O2 quickly in phosphate buffered solutions, which was comparable to CaO2 but faster than ZnO2 . Metal peroxides induced higher initial phenol degradation rates than UHP and H2 O2 when the same theoretic H2 O2 dosages and Fe(III)-EDTA were used. MgO2 displayed a superior performance for phenol degradation at pH 5, resulting in more than 93% phenol reduction at 1.5 h. According to kinetic analyses, the generation rate of in the MgO2 system was 18 and 3.4 times higher than those in ZnO2 and CaO2 systems, respectively. The addition of MgO2 significantly promoted H2 O2 based Fenton-like reactions by increasing production of, and the mixture of MgO2 and H2 O2 had an improved utilization efficiency of active oxygen than the MgO2 system. The findings suggested the critical roles of metal peroxides in favoring Fenton-like reactions and inspired strategies to simultaneously accelerate Fenton-like reactions and improve utilization efficiency of active oxygen. Graphical abstract: Image 1 Highlights: The performance of four solid peroxides in Fenton-like reactions were compared. generated from metallic peroxides is critical in promoting initial reactions. MgO2 has the highest production rate and reactivity for Fe(III)/Fe(II) recycles. A mixture of MgO2 and H2 O2 enhances the utilization efficiency of active oxygen.